1997
DOI: 10.21273/hortsci.32.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Spray Retention by Apple Leaves during a Growing Season

Abstract: Apple (Malus domestica Borkh.) leaves were sprayed to runoff using a selection of pesticides, and subsequent spray retention was evaluated by weight. Timing, cultivar, leaf surface, and leaf type significantly influenced spray retention. Spray retention correlated significantly and positively with leaf hair density. The importance of these differences is considered in relation to the possible efficiency of the pesticide application process in apple orchards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In the end we resorted to the observed average residues for the inside zone to initiate the model; this is the only model parameter obtained from the evaluation data. Spray retention of captan on leaves varies greatly within a growing season due to the change in canopy leaf density (Smith and MacHardy 1984) and surface structure (Hall et al 1997). Retention of a Zn tracer on apple fruit also varied greatly between years and between orchards (Xu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end we resorted to the observed average residues for the inside zone to initiate the model; this is the only model parameter obtained from the evaluation data. Spray retention of captan on leaves varies greatly within a growing season due to the change in canopy leaf density (Smith and MacHardy 1984) and surface structure (Hall et al 1997). Retention of a Zn tracer on apple fruit also varied greatly between years and between orchards (Xu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, in many practical situations the initial deposit is strongly influenced by variability in canopy structure, weather conditions and spray technology (Franz et al 1998;Walklate et al 2000;Xu et al 2006) but less dependent on the fruit area. Further, plant tissue surface structure can also greatly affect the initial deposit concentration (Smith and MacHardy 1984;Hall et al 1997). Thus, the initial deposit concentration varies greatly with crop growth stages.…”
Section: Model For Initial Depositsmentioning
confidence: 99%
“…This may be a result of rapid foliage expansion in apple trees from May to June with a plateau in July and little leaf growth in autumn. Once fully expanded (Hall et al, 1997), apple leaves may accumulate waxes subsequentially over the rest of the season, thereby influencing the retention of leafapplied agrochemicals. Moreover, the composition of epicuticular waxes varies considerably during a growing season as a result of different rates of production and transport of wax precursors to the leaf surface .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the cuticle prevents evaporative loss of water from the plant, but it is also the first interaction site for aerial insects, pathogens, and leaf-applied agrochemicals (Hull et al, 1975). The surface micromorphology, determined by characteristics of the cuticle, the epicuticular waxes deposited on it and trichomes, is of fundamental importance, especially in the case of pesticide adhesion and retention (Hall et al, 1997). The amount and composition of extruded waxes determine the leaf surface fine microstructure (Baker, 1982;Barthlott et al, 1998), having a great impact on surface wettability (Barnes et al, 1996;Beattie and Marcell, 2002) and cuticular penetration of externally applied products (Hunt and Baker, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…[10] The residues measured in individual supervised trials reflect the expectable residue levels following the practical use of pesticides according to the recommended maximum use patterns. However, the distribution of residues is very uneven within individual trees [17,18] and plots [19,20] and between treated fields [21,22] due to several factors including, for instance, the differences in the actual application rates and techniques, [23,24] spatial structure of canopy and leaf density [25,26] weather conditions [27] and growth dilution. [28] Statistical analysis of field to field variation of residues revealed that it can be described reasonably well with lognormal distribution having relative standard deviation of about 80%.…”
Section: Introductionmentioning
confidence: 99%